A Large Committed Long‐Term Sink of Carbon due to Vegetation Dynamics. Issue 10 (4th October 2018) - Pugh, T. A. M.; Jones, C. D.; Huntingford, C.; Burton, C.; Arneth, A.; Brovkin, V.; Ciais, P.; Lomas, M.; Robertson, E.; Piao, S. L.; Sitch, S.
Abstract: The terrestrial biosphere shows substantial inertia in its response to environmental change. Hence, assessments of transient changes in ecosystem properties to 2100 do not capture the full magnitude of the response realized once ecosystems reach an effective equilibrium with the changed environmental boundary conditions. This equilibrium state can be termed the committed state, in contrast to a transient state in which the ecosystem is in disequilibrium. The difference in ecosystem properties between the transient and committed states represents the committed change yet to be realized. Here an ensemble of dynamic global vegetation model simulations was used to assess the changes in tree cover and carbon storage for a variety of committed states, relative to a preindustrial baseline, and to attribute the drivers of uncertainty. Using a subset of simulations, the committed changes in these variables post‐2100, assuming climate stabilization, were calculated. The results show large committed changes in tree cover and carbon storage, with model disparities driven by residence time in the tropics, and residence time and productivity in the boreal. Large changes remain ongoing well beyond the end of the 21st century. In boreal ecosystems, the simulated increase in vegetation carbon storage above preindustrial levels was 20–95 Pg C at 2 K of warming, and 45–201 Pg C at 5 K, of which 38–155 Pg C was due to expansion in tree cover. Reducing the large uncertainties in long‐term commitment and rate‐of‐change of terrestrial carbon uptake will be crucial for assessments of emissions budgets consistent with limiting climate change. Plain Language Summary: Changes in climate and atmospheric carbon dioxide concentration affect ecosystems. One result of these effects, projected by most vegetation models, is that the global land biosphere is expected to continue to provide a net uptake of carbon dioxide throughout the 21st century. Characterizing this is important for policy, as it influences the amount of carbon dioxide emissions reductions needed to limit global warming. However, the effects of such environmental changes on land ecosystems are not all realized instantly. Ecosystems may continue to react to a change in their wider environment for decades or centuries after that change has occurred. These delayed reactions are termed the committed change. We found widespread agreement among multiple vegetation models that land in the far north will continue to take up a large amount of carbon in the long‐term, as a result of committed responses to climate change and carbon dioxide increases. The magnitude of uptake varied between simulations and was partially driven by an advance of the northern treeline. A less consistent model response was found in the tropics. The large amount of carbon involved, and associated climate policy implications, illustrates the benefits of further measurements leading to more accurate vegetation model calibration. Key Points: Terrestrial vegetation composition and carbon storage continue to change very substantially after stabilization of climate Uncertainty in this committed carbon uptake is of the order of several hundred Pg C, complicating emission budget calculations Vegetation dynamics need to be more routinely represented in the coupled Earth System Models used to make climate projections